2010
DOI: 10.1111/j.1744-6570.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

General Mental Ability, Narrower Cognitive Abilities, and Job Performance: The Perspective of the Nested-Factors Model of Cognitive Abilities

Abstract: The nested-factors model is a well-established structural model of cognitive abilities in cognitive ability research but has not yet been used to investigate the role of cognitive abilities in job performance. Core assumptions of the nested-factors model are that a broad general mental ability (GMA) exists besides narrower abilities and that this GMA differs from the narrower cognitive abilities in breadth but not in subordination. The authors of this article propose that a recently emerging statistical techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 88 publications
7
112
0
2
Order By: Relevance
“…However, all correlations virtually doubled under correction. Lang, Kersting, Hü lsheger, and Lang (2010) report similar results from meta-analysis of 50 studies in Germany.…”
Section: Predicting Job Performance From Iq Scoressupporting
confidence: 63%
See 3 more Smart Citations
“…However, all correlations virtually doubled under correction. Lang, Kersting, Hü lsheger, and Lang (2010) report similar results from meta-analysis of 50 studies in Germany.…”
Section: Predicting Job Performance From Iq Scoressupporting
confidence: 63%
“…Apart from the traditional psychometrically validated instruments (e.g., Wechsler's Adult Intelligence Scale, Raven's Progressive Matrices, or the U.S. Employment Service's General Aptitude Test Battery), studies have included working memory tests, reading tests, scholastic aptitude tests (SATS) and university admission tests, all taken in meta-analyses as surrogate measures of IQ. Sometimes, a ''general'' factor has been deduced as a composite of ''special ability '' tests (e.g., perceptual speed, memory;Lang et al, 2010), or by renaming the construct ''general mental ability'' (GMA) as ''another name for g'' (James & Carretta, 2002, p. 13).…”
Section: The Many Surrogates Of Iq Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, cognitive ability is defined as a general mental capacity which includes many abilities -planning, problem solving, abstract thinking, quick learning and learning from experiences (Hunter & Schmidt, 1996;Ones, Dilchert, & Chockalingam, 2012). A number of studies support the relationship between cognitive ability and overall job performance (e.g., Lang et al, 2010). Furthermore, a recent systematic review of the research in the United States identified seven studies that found a correlation between teacher cognitive ability and student learning and achievement (Wayne & Youngs, 2003).…”
Section: Characteristics Of Effective Teachersmentioning
confidence: 99%